Hadith Transmission and Cultural Dissemination in the Indonesian Archipelago: The Role of Maulid al-Diba’i - Mohammad Iqbal; Muhammad Al Mighwar; Engkos Kosasih; Irwan Abdurrohman; Tajul Arifin (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the historical development of hadith transmission and its cultural dissemination in the Indonesian Archipelago through the Maulid al-Diba’i tradition. While hadith has historically been transmitted through formal scholarly mechanisms such as talaqqī, sanad verification, and codification, its dissemination has also developed through devotional and cultural practices embedded in Muslim communal life. This study aims to analyze the transmission of hadith from the early Islamic period to its cultural adaptation in Nusantara, with particular focus on the role of Maulid al-Diba’i as a medium of hadith-related dissemination. This research employs a qualitative library research design using a descriptive-thematic content analysis approach. Primary data were drawn from the text of Maulid al-Diba’i, while secondary sources included classical hadith literature, studies on hadith transmission, and scholarship on living hadith and Islamic cultural traditions in Indonesia. The findings reveal that hadith transmission initially developed through direct oral learning, memorization, and communal teaching during the prophetic era, later evolving into more structured scholarly verification through sanad criticism and codification. In the Indonesian Archipelago, hadith dissemination expanded beyond formal scholarly institutions through cultural and devotional practices. The Maulid al-Diba’i functions as an important medium for transmitting hadith-related content concerning the Prophet’s lineage, virtues, moral excellence, and life journey through oral recitation, ritual performance, and communal participation. This study concludes that the Maulid al-Diba’i serves as a bridge between classical hadith tradition and lived Muslim religiosity, demonstrating that cultural adaptation constitutes an effective and legitimate pathway for preserving and disseminating prophetic teachings across generations.